ESTIMATIVA DA REATIVIDADE DE FÊMEAS NELORE DURANTE MANEJOS REPRODUTIVOS - OLIVEIRA, Pedro Henrique Pereira,; COSTA, Everton Garcia Areco Ximenez,; BARBOSA, Taciara Aparecida Duarte,; VILELA, Reíssa Alves,; SANTOS, Tânia Mara Baptista, (ANAIS DO ENIC, 2025)
-